Ticagrelor reduces neutrophil recruitment and lung damage in abdominal sepsis. (June 2014) - Rahman, Milladur; Gustafsson, David; Wang, Yongzhi; Thorlacius, Henrik; Braun, Oscar Ö
Abstract Platelets play an important role in abdominal sepsis and P2Y12 receptor antagonists have been reported to exert anti-inflammatory effects. Herein, we assessed the impact of platelet inhibition with the P2Y12 receptor antagonist ticagrelor on pulmonary neutrophil recruitment and tissue damage in a model of abdominal sepsis. Wild-type C57BL/6 mice were subjected to cecal ligation and puncture (CLP). Animals were treated with ticagrelor (100 mg/kg) or vehicle prior to CLP induction. Edema formation and bronchoalveolar neutrophils as well as lung damage were quantified. Flow cytometry was used to determine expression of platelet–neutrophil aggregates, neutrophil activation and CD40L expression on platelets. CLP-induced pulmonary infiltration of neutrophils at 24 hours was reduced by 50% in ticagrelor-treated animals. Moreover, ticagrelor abolished CLP-provoked lung edema and decreased lung damage score by 41%. Notably, ticagrelor completely inhibited formation of platelet–neutrophil aggregates and markedly reduced thrombocytopenia in CLP animals. In addition, ticagrelor reduced platelet shedding of CD40L in septic mice. Our data indicate that ticagrelor can reduce CLP-induced pulmonary neutrophil recruitment and lung damage suggesting a potential role for platelet antagonists, such as ticagrelor, in the management of patients with abdominal sepsis.